(untitled) (Journal of Nobel Medical College, 2021)
Background: Death in diabetes mellitus occurs mostly due to co-morbidities and complications resulting from diabetes. To reduce morbidity and mortality, awareness regarding diabetes and its complications is necessary. The aim of the study is to assess the health care practices and co-morbidities associated with the disease. Materials and Methods: A descriptive cross-sectional study was conducted at community level (Kharji ward number 4) at Biratnagar. All diagnosed patients of type II diabetes mellitus ≥ 18 years of age were enrolled for the study. Data for socio-demographic factors and clinical status were collected by pretested semi structured Questionnaire. Random blood sugar was measured using a portable glucometer. Anthropometric measurements were done by measuring height and weight of participants and body mass index was calculated by standard formula. The data was analyzed using SPSS version 21.0. Results: Out of the total 205 participants, 55.7% were found to be within the age group of 45-64 years i.e. middle aged (55.6%). Almost equal participants of the male and female were found, 50.7% and 49.3% respectively. More participants were found of below poverty line 67.31%. More than half 47.8% of the participants were suffering from the diabetes for less than 5 years of duration. All most all participants 98.5% knew about diabetes and its complications. Majority of the respondents 62.4% were having co-morbidity, among them 34.6% of participants were having hypertension. Majority of the participants were utilizing private health care service 79%. Conclusion: The diabetic participants were mostly of middle age with almost equal number of male and female having adequate knowledge about diabetes. Hypertension was the most common co morbidity among participants and they preferred private health care service mostly.